Incorporating Islamic inputs in the teaching of microeconomics: the experience of IIUM - Barom, Mohd Nizam (Centre for Islamic Economics, Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia and International Institute of Islamic Thought, 2024)
This chapter gives an overview of the experience of IIUM in embodying Islamic inputs in the teaching of Principles of Microeconomics, the first course on microeconomics theory students have to take on their first year for their Bachelor of Economics programme at the Kulliyyah of Economics and Management Sciences. The aim of the course is to equip the students with essential components of microeconomics concepts and theories while at the same time expose students to Islamic perspectives of microeconomics at the introductory level. This would prepare them for deeper study of Islamic microeconomic concepts in comparison to mainstream microeconomics at higher levels. Students are assessed through assignments, quizzes and exams. The chapter also explains a step-by-step integration of Islamic input approach that can be used in the teaching process. Examples of the integration process are given, using concepts such as scarcity and allocative efficiency.